2008
DOI: 10.1007/s11099-008-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and photosystem 2 efficiency of two salt-adapted halophytic seashore Cakile maritima ecotypes

Abstract: The effects of salinity (0-400 mM NaCl, marked S 0 , S 100 , S 200 , and S 400 ) on growth, photosynthesis, photosystem 2 (PS2) efficiency, ion relations, and pigment contents were studied in two seashore Cakile maritima ecotypes (Tabarka and Jerba, respectively, sampled from humid and arid bioclimatic areas). Growth of Jerba plants was improved at S 100 as compared to S 0 . Tabarka growth was inhibited by salinity at all NaCl concentrations. Leaf sodium and chloride concentrations increased with medium salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 70 publications
2
28
1
Order By: Relevance
“…CHL has a direct association with light harvesting potential, and researchers considered it as an important factor for photosynthetic capacity (Metwali et al 2011). Megdiche et al (2008) also reported important roles for photosynthetic pigments content considering its direct association with salt tolerance. CHL is also correlated with light harvesting capacity and acts against salt-induced oxidative damage.…”
Section: Salt Tolerance and Associations Between The Traitsmentioning
confidence: 96%
“…CHL has a direct association with light harvesting potential, and researchers considered it as an important factor for photosynthetic capacity (Metwali et al 2011). Megdiche et al (2008) also reported important roles for photosynthetic pigments content considering its direct association with salt tolerance. CHL is also correlated with light harvesting capacity and acts against salt-induced oxidative damage.…”
Section: Salt Tolerance and Associations Between The Traitsmentioning
confidence: 96%
“…In higher plants, dissipation of excess photochemical energy is an immediate and finely turned response, which occurs through heat irradiation, alternate sinks for photosynthetic elements and down regulation of photosystem II Megdiche et al 2008). The photoreduction of oxygen is an important alternative sink for the consumption of excess energy but it is associated with an increase in the generation of ROS such as H 2 O 2 , O 2 Á-, OHÁ and 1 O 2 (Foyer and Harbinson 1994;Nicolas et al 2006;Tahkokorpi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity could also have a similar effect. The physiological processes affected by salinity include changes in plant growth [11], membrane permeability [12], mineral distribution [13], reduction in chlorophyll content [14][15], and decreased efficiency of photosynthesis [16][17]. Understanding the physiological mechanisms of various stress factors is critical in predicting the disturbances that influence plant growth and productivity.…”
mentioning
confidence: 99%